Abundant microzooplankton possibly cause ultrahigh seawater dimethylsulfide during Southern Ocean algal blooms. (March 2022) - Zhang, Miming; Booge, Dennis; Yan, Jinpei; Xu, Suqing; Liang, Chen; Wu, Yanfang; Yang, Bo; Wang, Jianjun; Zhao, Jun; Li, Dong; Pan, Jianming; Park, Keyhong
Graphical abstract: Highlights: Ultrahigh seawater DMS levels (>40 nM) were detected near the Antarctic Peninsula. Ultrahigh DMS was only found in waters of algal bloom and abundant microzooplankton. Grazing of abundant microzooplankton possibly cause the ultrahigh seawater DMS. Abstract: Oceanic dimethylsulfide (DMS) is hypothesized to impact cloud formation and consequently the solar radiation budget of Earth's surface. Ultrahigh seawater DMS concentrations, up to hundreds of nM, have been observed in the Southern Ocean, attributing to concurrent high phytoplankton biomass. However, phytoplankton biomass cannot fully explain the mechanism leading to those extreme values. Herein, measurements, including seawater DMS concentrations and other biological and environmental parameters, were collected in the water column during the austral summer of 2015–2016 at the tip of the Antarctic Peninsula. Notably, large-scale ultrahigh seawater DMS concentrations (up to 85.2 nM and generally above 40 nM in the upper layer) was observed only in areas with co-existing phytoplankton blooms and abundant microzooplankton (indicated by ciliates, whose abundance and biomass were above 1000 ind L -1 and 2 μg L -1, respectively), implying that the grazing of abundant microzooplankton possibly causes the ultrahigh seawater DMS concentrations during the bloom seasons in the Southern Ocean.